On Surface Durability（pitting） of Through IIardened Gears - Meng Jinxian; et al. (Jixie chuandong)
The main proccsscs and rcsults of test on surface durability （pitting） of 40Cr and 35CrMo through hardened gcars are presented. The distribution paremcters of fort data are cstimatcd and inspected with computer. The present work gives two curves of R-S-N and provides the contact endurance limits to predict the gcars life.